2011
DOI: 10.1007/s11103-011-9818-5
|View full text |Cite
|
Sign up to set email alerts
|

The localization of Tic20 proteins in Arabidopsis thaliana is not restricted to the inner envelope membrane of chloroplasts

Abstract: Tic20 is a central, membrane-embedded component of the precursor protein translocon of the inner envelope of chloroplasts (TIC). In Arabidopsis thaliana, four different isoforms of Tic20 exist. They are annotated as atTic20-I, -II, -IV and -V and form two distinct phylogenetic subfamilies in embryophyta. Consistent with atTic20-I being the only essential isoform for chloroplast development, we show that the protein is exclusively targeted to the chloroplasts inner envelope. The same result is observed for atTi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 36 publications
2
25
0
Order By: Relevance
“…Only if the two proteins, to which the GFP fragments are fused, are located in the same cellular compartment can a GFP signal be observed (34). As expected, if both fragments were in the cytosol or the IMS of chloroplasts was a GFP signal observed in the corresponding compartment (Fig.…”
Section: Resultssupporting
confidence: 70%
“…Only if the two proteins, to which the GFP fragments are fused, are located in the same cellular compartment can a GFP signal be observed (34). As expected, if both fragments were in the cytosol or the IMS of chloroplasts was a GFP signal observed in the corresponding compartment (Fig.…”
Section: Resultssupporting
confidence: 70%
“…Generality of this model is supported by the identification of a PSII biogenesis compartment in the cyanobacterium Synechocystis sp. PCC 6803 and a GFP-tagged Tic20 paralogue which was seen to be localized to specific regions of the chloroplast envelope in A. thaliana (28,29). The effect of light on the relocalization of the TIC and TOC import machinery to lobe junctions might be relevant to the light stimulation of chloroplast protein import which has been observed in C. reinhardtii and vascular plants (24,30).…”
Section: Discussionmentioning
confidence: 95%
“…The results showed that the CCVs that are close to, but not associated with, broken chloroplasts also could be labeled by antibodies raised against PsbO1, a subunit of the photosystem II (PSII) complex localized in the thylakoid membrane (Supplemental Figure 4B). Moreover, CCVs also contained Tic20-II, a protein from chloroplast inner envelope membranes (Machettira et al, 2011) (Supplemental Figure 5B). These results suggested that CCVs were generated from chloroplast membranes that were disrupted by CV.…”
Section: Targets Chloroplasts and Induces Vesicle Formation In Chlmentioning
confidence: 99%